PENGARUH PENGGUNAAN POCKET BOOK SISWA DENGAN TEKNIK EVALUASI MEDIA PUZZLE CERIA TERHADAP SIKAP ILMIAH SISWA - Sukroyanti, Bq Azmi (Lensa : Jurnal Kependidikan Fisika, 2016)
This study aims to determine the effect of using a pocket book with the evaluation technique of cheerful puzzle media on students' scientific attitude. This study uses a type of quasi-experiment. Data obtained by using questionnaire. The average score of scientific attitudes obtained by students is 38.9% for the experimental class and 35.9 for the control class. The scientific attitudes of the experimental and control classes are sufficient and less criteria for control, with percentages of 72% and 59%. The result of this research can be concluded that there is influence of using pocket book with evaluation technique of puzzle cheerful media toward student's scientific attitude